Analysis Of The Effect Of Social Security And Commission On Platform System Obscurity Among Student Drivers In Bandung City - Ari Assrishan Sosh Mantoro; Halimah Zahrah; Nilam Meylani; Siti Azmi Nur Islami; Zaid Abdul Hamid (CAKRAWALA : Management Science Journal, 2025)
This study aims to examine the impact of the unclear applicator system on social security fairness and commission deductions for student online motorcycle taxi drivers in Bandung City. The research is motivated by ongoing demonstrations demanding transparency, fair working conditions, and protection for drivers, particularly concerning the partnership status and high commission cuts of 30% or more. Using a mixed methods approach with sequential exploratory design, the study began with qualitative interviews to explore key issues, followed by a quantitative survey involving 97 respondents. Regression analysis revealed that 60.1% of the perceived system obscurity is influenced by two main factors: the commission system and lack of social security. However, only the commission variable showed a significant partial effect. These findings emphasize the urgency of improving transparency in commission policies and fostering open, two-way communication between applicators and drivers to build a fairer and more sustainable partnership model in the digital transportation platform sector.